The Israeli settler movement assessing and explaining social movement success - Hirsch-Hoefler, Sivan ca. 20./21. Jh; Mudde, Cas 1967- (Cambridge University Press, 2020)
The Israeli settler movement plays a key role in Israeli politics and the Arab-Israeli conflict, yet very few empirical studies of the movement exist. This is the first in-depth examination of the contemporary Israeli settler movement from a structural (rather than purely historical or political) perspective, and one of the few studies to focus on a longstanding, radical right-wing social movement in a non-western political context. A trailblazing systematic assessment of the role of the settler movement in Israeli politics writ large, as well as in relation to Israel's policy towards the West Bank, this book analyzes the movement both as a whole and as a combination of its parts (i.e. branches) - institutions, networks, and individuals. Whether you are a student, researcher, or policymaker, this book offers a comprehensive and original theoretical framework alongside a rich empirical analysis which illuminates social movements in general, and the Israeli settler movement in particular
Title from publisher's bibliographic system (viewed on 08 Dec 2020)
Keywords: Social movements / Israel; Land settlement / Israel; Right-wing extremists / Israel; Siedlungspolitik; Israel